Pengaruh Tax Avoidance dan Komisaris Independen Terhadap Cost of debt dengan Transparansi Perusahaan Sebagai Variabel Moderasi - Ba'diyatul Musrifa (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to examine the effect of tax avoidance and independent commissioners on csot of debt with company transparency as a moderating variable. The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) 2015-2019. Samples were taken using purposive sammpling and obtained 44 companies. This study uses multiple linear regression analysis and absolute difference test. The results of this study indicate that tax avoidance has a negative effect on cost of debt. Independent commissioner has no negative effect on cost of debt. Company transparency is able to weaken the negative effects of tax avoidance. Company transparency is able to weaken the negative influence of independent commissioners. Keywords: Tax avoidance, independent commissioner, cost of debt, company transparency